Gambaran Karakteristik Ibu yang Mempunyai Anak Berat Badan Rendah di Rumah Sakit Umum Daerah di Yogyakarta - Wiwi Kustio Priliana (Jurnal Keperawatan Notokusumo, 2015)
Background: Each year in the world is estimated at about 20 million babies are born with low birth weight, a social and public health burden in developing countries. Most of the birth of low birth weight babies (LBW) babies born prematurely due to (premature) and growth disturbance during unborn/growth retardation (IUGR). Maternal factors will also affect the incidence of child who was born with LBW. In Indonesia, the prevalence of low birth weight is 5-27%, while in Yogyakarta prevalence of LBW in 2007 amounted to 14%. The Objective: Describe the characteristics of mothers who have children of low birth weight . Method: Descriptive Analytic. The research sample of 40 mothers who have of LBW infants. Sampling with purposive sampling, where research in the NICU Ward in Hospital Wates 20 sample and Yogyakarta Hospital 20 sample for two month. Result: showed that the majority of infants are born with a gestational age <37 weeks in hospitals Wates. They are 11 people (55%) ,> 37 weeks 9 people (45 %) and Yogyakarta hospital are gestational age <37 weeks 15 people (75%),> 37 weeks are 5 people (25%). The mother's education is the low number of hospitals Wates 6 (30%), High number of 14 people (70%). Yogyakarta Hospital 7 low education (35%), high 13 (65%). Wates Hospital : Maternal age> 35 years 1 people (5%), <35 years of 19 people (95%) and Yogyakarta hospital : maternal age> 35 years of 3 people (15%), <35 years 17 people (85%). Conclusion: Most of the characteristics of mothers who gave birth to a child with BBL in hospitals Wates and Yogyakarta hospital: maternal age <35 years and gestation <37 week.